1999
DOI: 10.1016/s1097-2765(00)80335-4
|View full text |Cite
|
Sign up to set email alerts
|

Calnexin Discriminates between Protein Conformational States and Functions as a Molecular Chaperone In Vitro

Abstract: Although calnexin is thought to function as a molecular chaperone for glycoproteins, a prevalent view is that it cannot distinguish between protein conformational states, binding solely through its lectin site to monoglucosylated oligosaccharides. Using purified components in vitro, calnexin effectively prevented the aggregation not only of glycoproteins bearing monoglucosylated oligosaccharides but also proteins lacking N-glycans, an effect enhanced by ATP. It also suppressed the thermal denaturation of nongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
142
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(151 citation statements)
references
References 36 publications
(4 reference statements)
7
142
2
Order By: Relevance
“…42), to make them achieve their proper tertiary or quaternary structure (43). However, calnexin (44) and calreticulin (45) also have efficient oligosaccharideindependent chaperone activity in vitro.…”
Section: Fig 8 Thermal Stability Of Wild-type and Mutant Bmp-1fmentioning
confidence: 99%
“…42), to make them achieve their proper tertiary or quaternary structure (43). However, calnexin (44) and calreticulin (45) also have efficient oligosaccharideindependent chaperone activity in vitro.…”
Section: Fig 8 Thermal Stability Of Wild-type and Mutant Bmp-1fmentioning
confidence: 99%
“…CNX and CRT also associate with a thiol oxidoreductase, ERp57, which interacts with cysteines in the substrate glycoproteins (12,13). In addition to their well-characterized association with glycan moieties, both CNX and CRT have been shown to bind to unfolded unglycosylated polypeptides and prevent their aggregation in vitro (14,15). It remains to be seen whether this type of interaction observed in vitro has a counterpart in the ER of living cells.…”
mentioning
confidence: 99%
“…6). However, more recent experiments have indicated that both calnexin and calreticulin directly discriminate between protein conformational states, and that both proteins can function in vitro as chaperones for glycosylated, as well as nonglycosylated, substrates (7,8).…”
mentioning
confidence: 99%